Health Related Quality of Life Variation among Water Pipe (Argihla) Smokers in Baghdad, Iraq - Al-Easawi, Nada Abdul-Rahman Flaih; Almashhada, Shaimaa Abdul-Kareem Abdullah; Alrekabi, Abd-Alameer Naser Ghaloub (Al-Nahrain Journal of Science, 2018)
The effects of water pipe (argihla) smoking on Health Related Quality of Life (HRQOL) on male population of 200 in Baghdad, Iraq was investigated. Aquestionnaire regarding health survey consisted of short form questions (SF36) was grouped into 8-scales: Physical Functioning (PF), Social Functioning (SF), Role Physical (RP). Mental Health (MH), Energy/ Vitality, Bodily Pain (BP) and General Health (GH). The survery was summarized into two main aspects: Physical Component Summary (PCS) and Mental Component Summary (MCS). Results showed that the majority of argihla smokers aged between (20-29) years old. The smoking percentage of unmarried individuals is higher than that of married ones and it’s more dominant among college education level. More than half number of argihla smokers have occupations and most of them are already smoking cigarettes. The mean score of (PCS) subscales were lower than those of non smokers at all subscales except the bodily pain score. All mean score subscale belonging to (MCS) were low for argihla smokers as compared with non smokers. Regression analysis revealed that old aged smokers with allergic and asthmatic diseases are those whom consume argihla weekly, and the employed smokers were the most important independent explanatory variable of the poorest (PCS) while the most explanatory variable of poorest (MCS) are represented by those of the college educational level, cigarette smokers, old aged whom suffering allergic and asthmatic diseases.